ANALISA PENGANGGURAN DI INDONESIA - Riska Franita; Andes Fuady Dharma Harahap; Yani Sukriah (Universitas Muhammadiyah Tapanuli Selatan, 2019)
The high unemployment rate, a problem that must be solved because it will have implications for economic development. The government is expected to be overcome with cultivate the spirit of entrepreneurship, SMEs (small medium enterprises) by providing training - training to the unemployed. The role of education also participate in the creation of superior human resources in order to compete in the free market and to reduce unemployment. Because pengaguran very bad for economic, social, and mental. Immediately followed up with the problem of unemployment will impact on the creation of an independent community. and will increase the economic growth of a nation.